Prevalence of Menstrual Dysfunction and Hormonal Contraceptive Use Among Elite Female Athletes from Different Sports in Germany - Elisabeth M. Kirschbaum; Katharina Fischer; Dorothee Speiser; Franziska Lautenbach; Friedemann Schwenkreis; Anne Dathan-Stumpf; Kirsten Legerlotz (Sports Medicine - Open)
Abstract Background While a regular menstrual cycle is an indicator of good health, menstrual dysfunction (MD) and wrong beliefs regarding hormonal contraceptives (HC) are quite common among elite female athletes and threaten their health. This study aimed to (1) identify the prevalence of current and lifetime MD in various sports disciplines, (2) investigate variables that are associated with the prevalence of MD, (3) study the current practice of HC use among elite German female athletes. Methods 584 German elite female athletes (mean 20.7 ± 4.9 years) from 64 different sports completed an online questionnaire to assess gynecological health characteristics, history of MD, and the use of HC. Results Sixty-nine percent of athletes not using HC reported a regular menstrual cycle, while oligomenorrhea was currently reported in 13%, secondary amenorrhea in 8%, primary amenorrhea in 2% and polymenorrhea in 8%. The current prevalence of primary amenorrhea differed between sports disciplines (p = 0.002), while oligomenorrhea (p = 0.828) and secondary amenorrhea (p = 0.848) did not. The lifetime prevalence of primary amenorrhea (10%) and oligomenorrhea (74%) differed significantly between sports disciplines (p < 0.001 and p = 0.001), while secondary amenorrhea (40%) did not (p = 0.298). The current and lifetime prevalence of primary amenorrhea was higher in aesthetic sports disciplines, while the lifetime prevalence of oligomenorrhea was higher in endurance disciplines. Factors associated with lower prevalences of MD were menstrual cycle tracking (p < 0.001), higher gynecological age (p < 0.001), regular gynecological health screenings (p = 0.008), and a diagnosed eating disorder (p = 0.037). Twenty-nine percent of these elite athletes used HC, of whom 15% claimed to use HC as a treatment for MD. Conclusion Elite female athletes from a variety of sports disciplines, not just from endurance and aesthetic sports, are at high risk of developing MD. Given the high percentage of athletes using HC to treat MD, educating athletes, coaches, others from the support team and parents about the risk and prevention of MD and the effects of HC in the context of elite sports may improve gynecological health among elite athletes.